Barriers to Compliance with Library Standards in Ugandan Universities - Odong, Patrick; Magara, Elisam; Nabutto, Clement Lutaaya (Eastern African Journal of Humanities and Social Sciences, 2025)
University libraries are essential in supporting teaching, learning, and research; however, several universities failed to achieve the minimum requirements as envisaged by the National Council for Higher Education (NCHE) and international bodies like IFLA because they face many systemic and institutional problems. Therefore, the study investigated the barriers affecting compliance with library standards by Ugandan universities, as discussed in this study, with a view to enlightenment on institutional, technological, and regulatory hindrances to effective library service delivery. Data collection was carried out through a mixed-methods research design under a pragmatic paradigm in 12 universities through questionnaires (n = 433), interviews, participant observations, and document reviews. Findings revealed that limited funding, outdated and inadequate information resources, poor ICT infrastructure, unstable power supply, inadequate reading space, understaffing, and low staff capacity greatly impacted the compliance levels. High enrolment of students vis-a-vis the gradual expansion of library services, poor enforcement of policy, and negative attitudes towards the library from stakeholders further aggravate the non-compliance issue. The study, therefore, concludes that most of the universities did not attain the minimum levels of NCHE standards owing to systemic and operational problems. Hence, it is recommended that regulatory oversight be strengthened, institutional investment increased, staff trained continuosly, content developed within the country, and engagement of users promoted toward filling in these gaps. These findings therefore provide a basis for further advocacy on policy formulation and institutional reforms toward improving library services in Uganda's higher education institutions.